THEORETICAL FOUNDATIONS OF CRITICAL THINKING OF STUDENTS IN THE CONDITIONS OF INNOVATION EDUCATION - Nasimova , Zarina Isomiddin qizi (Educational Research in Universal Sciences, 2023)
The educational process is the process of connecting new ones with known ones. The new imagination of the reader is built on the basis of his previous knowledge and imagination. By helping students regain their previous knowledge and imagination, a broad framework can be laid for a long-term understanding of new information.